Data on microbial DNA-induced IL-1β production in monocytes of type 1 diabetes patients - Zentsova, Irena; Parackova, Zuzana; Kayserova, Jana; Palova-Jelinkova, Lenka; Vrabcova, Petra; Volfova, Nikol; Sumnik, Zdenek; Pruhova, Stepanka; Petruzelkova, Lenka; Sediva, Anna (Data in brief, 2019)
Inflammasomes are large protein complexes involved in the maturation of IL-1β, a cytokine associated with the pathophysiology of type 1 diabetes (T1D). The data presented in this article focused on the role of inflammasomes in DNA recognition in T1D patients. This data extend knowledge on DNA sensing in T1D patients and relate to our research paper "Monocytes contribute to DNA sensing through the TBK1 signaling pathway in type 1 diabetes patients" Zentsova et al., 2009. To examine inflammasome involvement, we blocked the known mechanism of inflammasome activation - potassium efflux via various approaches: 1) high concentration of KCl; 2) Glybenclamide, which selectively blocks the ATP sensitive K+ channel; 3) KN-62, an inhibitor of P2X7 receptor, which activates K+ channel after ATP binding. Moreover, we used an inhibitor which blocks Nod-like receptor family containing pyrin domain 3 (NLRP3) inflammasome. In T1D patients, we show that secretion of cytokines IL-1β, TNFα, IL-6 and IFNα after microbial DNA stimulation is promoted by potassium efflux and is not dependent on P2X7 receptor signaling. Surprisingly, the microbial DNA induced IL-1β release was independent of NLRP3.
Keywords: Glybenclamide; DNA; Monocytes; Inflammasomes; NLRP3; Type 1 diabetes